Pengembangan UMKM Di Desa Pantai Bhakti Muara Gembong, Bekasi Melalui Kreativitas dan Inovasi - Nathadiharja, Sri Sukartono; Diansyah, Diansyah; Tambun, Sihar (Jurnal Pemberdayaan Nusantara, 2024)
Community service activities through the Student Work Lecture (KKM) program. In improving the village economy through Community service activities through the Student Work Lecture (KKM) program. In improving the village economy in development through creativity and innovation, Pantai Bhakti Village, Muara Gembong, Bekasi, has potential natural resources that can support the development of Micro, Small and Medium Enterprises (UMKM). However, limitations in terms of creativity, innovation, and market access are still an obstacle for local communities in optimally developing their UMKM. This community service program aims to increase the capacity of UMKM in Pantai Bhakti Village through training that focuses on product creativity, innovation in seafood processing, and digital marketing strategies. Through a participatory approach, the community is given an understanding of unique and valuable product development, digital-based marketing techniques, and sustainable utilization of local resources. The results of the program showed an increase in the community's ability to create innovative products and expand their marketing reach. This article reviews the role of creativity and innovation as key to UMKM development in coastal areas and the importance of collaborative support to achieve local economic sustainability.